Reported linear sedimentation (LSR) and mass accumulation rate (MAR), as well as corrected mean MAR pre-1975 and post-1975 in the inner Gulf of Thailand - Bingbing Wei (PANGAEA, 2025)
This dataset includes sediment accumulation rates in the inner Gulf of Thailand, derived from published data (Boonyatumanond et al., 2007; Bidorn et al., 2021; Chaisanguansuk et al., 2023; Cheevaporn et al., 1994; Guo et al., 2018; Srisuksawad et al., 1997; Windom et al., 1984), and recalculated to generate changes in mass accumulation rate before and after 1975, with a MAR rising factor of 2.5 in nearshore cores and 1.3 in offshore cores (see related paper for details).